Long-term follow-up of linear scleroderma en coup de sabre in children with central nervous system involvement - Chang, Xingzhi; Ren, Lihong; Wu, Ye; Zhang, Yuehua; Wei, Cuijie; Zhang, Qingping; Zhang, Meijiao; Zhao, Chunyan; Bao, Xinhua (Frontiers in Immunology, 2026)
IntroductionLinear scleroderma en coup de sabre (ECDS) is a rare disorder that often involves the central nervous system (CNS), requiring systemic immunotherapy. This study characterizes the clinical and neuroimaging features as well as the long-term treatment outcomes of pediatric ECDS.MethodsPatients with ECDS and CNS involvement were enrolled. Clinical manifestations, cranial imaging, pathology, and immunotherapy responses were documented.ResultsSeven patients (6 females and 1 male) were included, with onset ages ranging from 1.8 to 13.5 years. Rash preceded neurological symptoms in five patients; seizures were the initial manifestation in the remaining two. Seizures were the most common neurological symptom (5/7), followed by dizziness (3/7), movement disorder (2/7), blurred vision (1/7), and headache (1/7). All exhibited ipsilateral supratentorial MRI abnormalities, exclusively on the left side and predominantly frontal. White matter lesions were observed in all patients, and cyst-like lesions were identified in four. Brain biopsy performed in two patients indicated vasculitis. All received systemic corticosteroids, either alone (2 cases) or combined with other agents (methotrexate in 5, mycophenolate mofetil in 3, IVIg in 3, tocilizumab in 2, and rituximab in 1). Over 6 months to 15 years of follow-up, neurological symptoms resolved in five patients. Skin lesions progressed in three patients, stabilized in two, and improved in two.ConclusionLinear scleroderma en coup de sabre with CNS involvement predominantly affects females and typically involves the left cerebral hemisphere. Characteristic brain MRI findings include ipsilateral supratentorial white matter abnormalities and cyst-like lesions. Combination therapy with systemic corticosteroids and methotrexate is recommended as first-line treatment, while tocilizumab may be beneficial for refractory cases.